A Systematic Review of Early Warning Systems' Effects on Nurses' Clinical Performance and Adverse Events Among Deteriorating Ward Patients. Issue 3 (September 2020) - Lee, Ju-Ry; Kim, Eun-Mi; Kim, Sun-Aee; Oh, Eui Geum
Abstract : Objective: Early warning systems (EWSs) are an integral part of processes that aim to improve the early identification and management of deteriorating patients in general wards. However, the widespread implementation of these systems has not generated robust data regarding nurses' clinical performance and patients' adverse events. This review aimed to determine the ability of EWSs to improve nurses' clinical performance and prevent adverse events among deteriorating ward patients. Method: The PubMed, CINAHL, EMBASE, and Cochrane Library databases were searched for relevant publications (January 1, 1997, to April 12, 2017). In addition, a grey literature search evaluated several guideline Web sites. The main outcome measures were nurses' clinical performance (vital sign monitoring and rapid response team notification) and patients' adverse events (in-hospital mortality, cardiac arrest, and unplanned intensive care unit [ICU] admission). Results: The search identified 888 reports, although only five studies fulfilled the inclusion criteria. The findings of these studies revealed that EWSs implementation had a positive effect on nurses' clinical performance, based on their frequency of documenting vital signs that were related to the patient's clinical deterioration. In addition, postimplementation reductions were identified for cardiac arrest, unplanned ICU admission, and unexpected death. Conclusions: It seems that EWSs can improve nurses' clinical performance and prevent adverse events (e.g., in-hospital mortality, unplanned ICU admission, and cardiac arrest) among deteriorating ward patients. However, additional high-quality evidence is needed to more comprehensively evaluate the effects of EWSs on these outcomes.